An Improved MPCC Method Based on the Predictive Delay Error Analysis for PMSM Speed Control System. Issue 1 (May 2021) - Tang, Siyuan; Wang, Ying
Abstract: Taking permanent magnet synchronous motor (PMSM) as the research object, the model predictive current control strategy (MPCC) was studied. In order to solve the shortcoming that the MPCC strategy depends on the motor prediction model, reduce the prediction error caused by MPCC and enhance the prediction accuracy of the system, an improved MPCC model was constructed by a two-step prediction method. At the same time, compared with the system based on Field-Oriented Control (FOC) and MPCC control and the system based on improved MPCC control, the proposed control strategy can make the PMSM run stably and efficiently, and reduce the torque ripple and the THD value of the three-phase stator resistance current. The simulation results show that the motor system controlled by the method can run stably, and then the correctness and effectiveness of the strategy are verified.